Adherence to the headache diary in a specialized outpatient clinic of a tertiary service in Fortaleza - Carvalho, Pedro Rubens Araújo; Queiroga, Morgana Feitosa de; Sampaio, Rhina de Freitas; Neri, Pedro Vinicius da Silva; Lima, Gabrielle Benevides; Assunção, Robson Caetano Guedes; Guedes, Matheus da Costa; Lira, Lucas Antônio Martins; Silva, Carla Welch da; Lôbo, Camila de Oliveira; Ramalho, Erika Queiroga; França, Mário Hermes Rios; et al. (Headache Medicine, 2023)
Full abstract in PDF.